SAT0014 DECREASED CIRCULATING CD19+CD24HICD38HIREGULATORY B CELLS IN ACPA POSITIVE RHEUMATOID ARTHRITIS: EFFECT OF IL-6 RECEPTOR BLOCKADE. (June 2019) - Fortea-Gordo, Paula; Villalva, Alejandro; Nuño, Laura; Santos-Bornez, Maria-Jose; Monjo, Irene; Peiteado, Diana; Puig-Kröger, Amaya; Sanchez-Mateos, Paloma; Balsa, Alejandro; Miranda-Carus, Maria-Eugenia
Abstract : Background: CD19+CD24 hi CD38 hi B cells have a regulatory capacity and their frequency is altered in the peripheral blood of patients with various autoimmune conditions, including RA. Objectives: To determine the frequency of circulating CD19+CD24 hi CD38 hi regulatory B cells (cBreg) in ACPA+ vs ACPA- patients with RA, and its possible modification by IL-6R blockade. Methods: Peripheral blood was drawn from ACPA+ (n= 37) or ACPA- (n=19) RA patients treated with conventional synthetic DMARDs (csDMARDs), and from ACPA+ (n=31) or ACPA- (n=12) RA patients treated with tocilizumab; in additon one age and gender-matched healthy control was studied alongside with each patient (n= 99). After isolation by Ficoll-Hypaque gradient, PBMCs were stained with antibodies to CD3, CD4, CD19, CD24, and CD38, and examined by flow cytometry. Results: A decreased frequency of cBreg cells was observed in ACPA+ but not ACPA- RA patients treated with csDMARDs. Interestingly, the frequency of cBreg cells showed a significant negative correlation with ACPA titers (r = -0.44, p = 0.021). In contrast, no correlation was found between the frequency of cBreg cells and either RF titres or disease activity as determined by the DAS28 score. However, not only in ACPA- but also in ACPA+ patients receiving tocilizumab, the percentage of cBreg cells was not different from that observed in HC. Four ACPA+ patients treated with csDMARDs who initiated tocilizumab, demonstrated a significant elevation of their cBreg frequency at 12 months. Conclusion: A decreased frequency of cBreg cells is apparent in ACPA+ but not ACPA- RA patients receiving csDMARDs, that is related with ACPA titres but not with RF titres or disease activity. In contrast, in ACPA+ patients treated with tocilizumab, the frequency of CD19+CD24 hi CD38 hi B cells is comparable to that observed in HC, suggesting that IL-6R blockade is able to modify the altered Breg cell balance. Reference: [1] Flores-Borja F, et al. Sci Transl Med. 2013;5:173ra23. Disclosure of Interests: Paula Fortea-Gordo: None declared, Alejandro Villalva: None declared, Laura Nuño: None declared, Maria-Jose Santos-Bornez: None declared, Irene Monjo: None declared, Diana Peiteado: None declared, Amaya Puig-Kröger: None declared, Paloma Sanchez-Mateos: None declared, Alejandro Balsa Grant/research support from: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Consultant for: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Sandoz, Lilly, Paid instructor for: Pfizer, Speakers bureau: Pfizer, Novartis, UCB, Nordic, Sanofi, Sandoz, Lilly, Maria-Eugenia Miranda-Carus Grant/research support from: Roche Pharma, BMS